Photo-Oxidation of Thiouracil by Singlet Oxygen - Mehta, Prabha; Mehta, S.C. (Asian Journal of Chemistry, 2010)
Photo-oxidation of thiouracil was carried out using eosin yellow, rose bengal and methylene blue as dye sensitizers. After completion of reaction two products were isolated and characterised as thiourea and acetyl thiourea by physical, chemical and spectral methods. A mechanism has been proposed for this reaction.